Effect of H2O-Based Low-Pressure Plasma (LPP) Treatment on the Germination of Bambara Groundnut Seeds - Naeem Ahmed; Asad Masood; Kim S. Siow; M. F. Mohd Razip Wee; Rahmat Zaki Auliya; Wai Kuan Ho (Agronomy, 2021)
In general, seed germination is improved by low-pressure plasma (LPP) treatment using precursors such as air, nitrogen, argon, or water (H2O). Here, H2O-based LPP treatment using the optimized parameters of 10 W and 10 s improves the germination of Bambara groundnut seeds by 22%. LPP increases the wettability and roughness of the seed hilum while oxidizing the surface with carboxyl and amine groups. In this H2O-based treatment of Bambara groundnut seeds, combinatory etching and chemical modification facilitated the imbibition process and increased the germination percentage. The success of this method has the potential to be scaled up to solve food security with seeds otherwise facing germination-related issues.